PENGEMBANGAN BUKU AJAR FITOREMEDIASI UNTUK MATAKULIAH PENCEMARAN LINGKUNGAN - Haslinda Yasti Agustin (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2017)
The purpose of this study is to produce products such as phytoremediation handbook for the course of Environmental Pollution. This study uses a model of research and development Borg & Gall until the fifth stage is a major product revision. Data obtained from the handbook development expert validation sheet material, teaching materials experts, education professionals (lecturers), and students, who then all the data is analyzed. The results of the validation calculation shows the results valid and sufficient valid and does not need revision, but the revision is still being done by taking into account suggestions and comments provided by all validator to fix the product. Results of the study are the product of the handbook entitled